Establishment of an Administered Account for Interim Holdings of Voluntary Contributions for Fund Activities and Establishment of a Framework Administered Account for Selected Fund Activities : Subaccount for the Administration of Selected Smaller-Scale Capacity Building Activities. (Policy Papers; Policy Paper, 2010)
This paper identifies policy tools to support fiscal consolidation in the years ahead. Its starting point is the analysis in the recent Board papers describing strategies for fiscal consolidation (IMF, 2010a, 2010b), which showed that on current trends, general government debt in advanced countries would rise 36 percentage points of GDP during 2007-14, and that age-related spending (health and pension) would rise rapidly later, further adding to fiscal pressures. Trends are more favorable in emerging economies, but adjustments are needed there too.